Antioxidant Assay and Antifungal Activity of Essential Oil and Various Extracts from Alpinia allughas Roscoe: A Potent Zingiberaceous Herb. Issue 2 (17th February 2016) - Sethi, Sonali; Prakash, Om; Punetha, H.; Pant, A.K.
Abstract: The present study describes antifungal activities and antioxidant assays of essential oil and different extracts from Alpinia allughas (Zingiberaceae) rhizomes. The essential oil was found to be remarkable fungicide according to its inhibition action against all tested pathogens like Colletotricum falcatum, Rhizoctonia solani, Sclerotinia sclerotium and Sclerotium rolfsii followed by different extracts obtained in dichloromethane, methanol, hexane and petroleum ether respectively with their MIC values ranging from 31.25 to 500 μg/ml. The essential oil showed higher phenolic contents (61.33 μg/ml) than the extracts. The antioxidant assay evaluated in essential oil and extracts by different methods revealed good to moderate antioxidant potential with different values viz. (160.77-239.17 μg/ml) in Fe3+ reducing power, (86.10-217.08 μg/ml) in Fe 2+ metal chelating ability, (59.12-137.28 μg/ml) in DPPH, (59.07-145.03 μg/ml) in OH radical, (69.70-161.32 μg/ml) in NO radical and (49.38-229.58 μg/ml) in superoxide anion scavenging activities respectively in comparison to the standard antioxidants, BHT, catechin, gallic acid and ascorbic acid. Based on the aforementioned results obtained, the herb A. allughas can be a good source to develop a safe, ecofriendly and sustainable natural, food preservative.